Preface to the Special Issue on "The Impact of Resilience in Developing Individual and Organizational Capacity to 'Bounce Back' from Challenges". Issue 4 (November 2020) - Bal, Matthijs
The Problem: Stress, anxiety, depression, and similar emotional and psychological inhibitors may negatively impact employee well-being and dignity, quality of work-life, and overall organizational performance. These inhibitors may be produced through events such as structural or procedural changes, tensions emanating from diminished work relationships, pressures related to the work itself, perceptions of unjust or unfair treatment, or other forces that may affect an individual's capacity to function and perform well. The Solution: This Special Issue explores approaches to gain insight to the ways individuals, as well as the organizations they serve, may become more resilient and bounce back from adversity. The interdisciplinary relationship between human resource development (HRD) and human resource management (HRM) is crucial for effective strategies to overcome negative outcomes. The Stakeholders: HRD scholars, practitioners, researchers, and all other professionals concerned with optimizing employee well-being and optimizing the capacity to perform will benefit from this Special Issue.